2020
DOI: 10.33448/rsd-v9i11.10091
|View full text |Cite
|
Sign up to set email alerts
|

Práticas de ajardinamento em espaços de convivência em comunidades rurais como instrumento de Educação Ambiental

Abstract: A ornamentação de espaços de convivência social proporciona a seus usuários vários benefícios em comunidade, especialmente, o embelezamento destes espaços, tornando-os mais prazerosos e uteis. O presente trabalho teve como objetivo desenvolver ações relacionadas à Educação Ambiental por meio de práticas de paisagismo e ajardinamento de espaços de convívio social de comunidades rurais. Valorizando a cultura e a preservação da vegetação destes espaços, através de oficinas, que ocorreram em conjunto com a Prefeit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Sweet ex Klatt, popularly known as African iris or butterfly iris, belongs to the family Iridaceae and probably constitutes the most basal old-world member of the tribe Irideae (Goldblatt and Manning, 2008a). It is an ornamental species of increasing commercial value (Ayoub et al, 2018;Menegaes et al, 2020), which can also be used for medicinal purposes as a potential source of natural antibacterial and antifungal agents (Ayoub et al, 2018). Recent studies have shown the effects of plant growth regulators on in vitro germination and development of D. bicolor seedlings, although the germination percentage was low .…”
Section: Introductionmentioning
confidence: 99%
“…Sweet ex Klatt, popularly known as African iris or butterfly iris, belongs to the family Iridaceae and probably constitutes the most basal old-world member of the tribe Irideae (Goldblatt and Manning, 2008a). It is an ornamental species of increasing commercial value (Ayoub et al, 2018;Menegaes et al, 2020), which can also be used for medicinal purposes as a potential source of natural antibacterial and antifungal agents (Ayoub et al, 2018). Recent studies have shown the effects of plant growth regulators on in vitro germination and development of D. bicolor seedlings, although the germination percentage was low .…”
Section: Introductionmentioning
confidence: 99%
“…Sendo que, os vegetais por suas características naturais, proporcionam muitos benefícios aos seres humanos, sob vários aspectos, tais como: geram bem estar psicológico; melhoram o efeito estético da paisagem; proporcionam sombra para os pedestres e veículos; protegem do vento; amenizando a poluição sonora; reduzem o impacto da água de chuva e seu escorrimento superficial; auxiliam na diminuição da temperatura e refrescam o ambiente; melhoram a qualidade do ar entre outros (Alves et al, 2020;Barbosa et al, 2020;Menegaes et al, 2020;Pivetta & Silva Filho, 2002). Além de a arborização colaborar de forma significativa para a melhoria do conforto urbano, também é um elemento de contemplação, fornecedora de flores e frutos atrativos, e centro de configuração paisagística, como ponto de referência para orientação e identificação, que aproxima os seres humanos do convívio com a natureza, mesmo em espaços urbanizados (Porto & Brasil, 2013).…”
Section: Introductionunclassified